1996
DOI: 10.1007/bf03017958
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecally administered NMDA receptor antagonists reduce the MAC of isoflurane in rats

Abstract: Purpose: We studied the effects of intrathecal administration of an N-methyl-D-aspartate (NMDA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…GABA and glutamate are major neurotransmitters in spinal cord inhibitory and excitatory circuits, and it has been reported that volatile anesthetics can act on both receptors [5][6][7][8]. Furthermore, it has been shown that intrathecal administration of a GABA A receptor agonist or a glutamate receptor antagonist reduces the minimum alveolar anesthetic concentration (MAC; the anesthetic concentration that prevents movement in response to supramaximal stimulation in 50% of animals) of volatile anesthetics [9][10][11]. Therefore it is hypothesized that one or both of these receptors may be involved in the mechanism by which volatile anesthetics produce immobility.…”
mentioning
confidence: 99%
“…GABA and glutamate are major neurotransmitters in spinal cord inhibitory and excitatory circuits, and it has been reported that volatile anesthetics can act on both receptors [5][6][7][8]. Furthermore, it has been shown that intrathecal administration of a GABA A receptor agonist or a glutamate receptor antagonist reduces the minimum alveolar anesthetic concentration (MAC; the anesthetic concentration that prevents movement in response to supramaximal stimulation in 50% of animals) of volatile anesthetics [9][10][11]. Therefore it is hypothesized that one or both of these receptors may be involved in the mechanism by which volatile anesthetics produce immobility.…”
mentioning
confidence: 99%
“…The subarachnoid catheter was flushed with 0.3 mL normal saline after intrathecal administration, and all the dogs were allowed to move freely. Motor and sensory blockades, as well as the consciousness state of the dogs, were observed at 20 and 40 seconds and at 1, 3,5,10,15,20,25,30,35,40,45,60,75, and 90 minutes and then 120 minutes after administration of these drugs, according to the evaluation scales as shown in Table 1A. 1 The dogs' state of consciousness was scored according to a 4-point scale (Table 1A), and motor blockade of limbs was evaluated according to a 3-point scale (Table 1A).…”
Section: Experiments 1: Subarachnoid Anesthetic Effect Of 8% Ei In Beamentioning
confidence: 98%
“…Entretanto, alguns estudos sugeriram um possível efeito supra-espinhal sobre a atividade dos receptores NMDA medulares. Masaki e col. 71 notaram a redução da CAM do sevoflurano após aplicação intraventricular de D-AP5 (um antagonista NMDA), enquanto Ishizaki e col. 72 encontraram uma redução máxima de 30% na CAM do isoflurano em ratos após administração subaracnóidea de AP5, MK-801, CPP e 7CKA (antagonistas NMDA). Esses resultados sugeriram, então, um efeito predominantemente supra-espinhal dos anestési-cos inalatórios sobre receptores NMDA.…”
Section: Mediadores Possivelmente Relevantesunclassified
“…Some studies, however, have suggested a possible supraspinal effect on spinal NMDA receptors activity. Masaki et al 71 have shown sevoflurane MAC decrease after brain intraventricular administration of D-AP5 (NMDA antagonist), while Ishizaki et al 72 have found a maximum 30% decrease in isoflurane MAC in rats after spinal administration of AP5, MK-801, CPP and 7CKA (NMDA antagonists). These results have then suggested a predominantly supraspinal effect of inhalational anesthetics on NMDA receptors.…”
Section: Probably Relevant Mediatorsmentioning
confidence: 99%